1979
DOI: 10.1007/bf01953236
|View full text |Cite
|
Sign up to set email alerts
|

Effect of organophosphate pesticide Sumithion (Fenitrothion) on some aspects of carbohydrate metabolism in a freshwater fish,Sarotherodon (Tilapia)mossambicus (Peters)

Abstract: A lethal (Lc50/48 h - 6 mg/l) concentration of the organophosphate (OP) pesticide Sumithion increased blood glucose levels and phosphorylase activity, but hepatic glycogen registered a fall which indicated that the observed hyperglycemia was due to breakdown of hepatic glycogen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
1

Year Published

1982
1982
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 4 publications
4
13
1
Order By: Relevance
“…Sastry and Siddiqui (1984) reported increase in the glycogen content of liver and muscle of Channa punctutus after exposure to quinalphos. Contrary to that and in agreement with the present results Koundinya and Ramamurthi (1979) observed hyperglycemia accompanied by decrease in the glycogen content of liver and muscle of Sarotherodon mossambica after treatment with fenitrothion.…”
Section: Resultscontrasting
confidence: 56%
“…Sastry and Siddiqui (1984) reported increase in the glycogen content of liver and muscle of Channa punctutus after exposure to quinalphos. Contrary to that and in agreement with the present results Koundinya and Ramamurthi (1979) observed hyperglycemia accompanied by decrease in the glycogen content of liver and muscle of Sarotherodon mossambica after treatment with fenitrothion.…”
Section: Resultscontrasting
confidence: 56%
“…Fenitrothioninduced increase in blood glucose in S. mossambicus was associated with decreased hepatic glycogen (Koundinya and Ramamurthi, 1979) and sub chronic exposure of rats to acephate, which caused slight increase in blood glucose, also caused depletion of liver glycogen (Deotare and Chakrabarti, 1981). Abdollahi et al (2004a) reported increased activity of GP and phosphoenolpyruvate carboxykinase (PEPCK) following sub chronic exposure to Malathion.…”
Section: Discussionmentioning
confidence: 97%
“…Fenitrothion and fenthion have been shown to increase blood glucose levels in S. mossambicus, a fresh water fish (Koundinya and Ramamurthi, 1979) and H. fossilis, a teleost fish (Srivastava and Mishra, 1983), respectively following acute exposure. Acute exposure to malathion (Matin and Hussain, 1987;Panahi et al, 2006) and diazinon (Hussain and Ansari, 1988;Matin et al, 1989) has also been shown to be associated with elevated blood glucose in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 2 illustrates how disturbances in the histoarchitecture of the liver induced by OPs can affect its performance in the enzymatic pathways involved in the metabolism of lipids, carbohydrates, and proteins in the cytoplasm, mitochondria, and peroxisomes (9). Animal studies suggest that the activity of glycogen phosphorylase (GP), the enzyme that breaks glycogen into glucose and reduces the hepatic glycogen content, increases after fenitrothion and malathion exposure (74,75). This is supported by a drop in hepatic glycogen concentration after fenthion exposure in fish (76).…”
Section: Possible Effects Of Ops On Hepatic Carbohydrate Lipid and mentioning
confidence: 99%